(untitled) (REMUNOM, 2024)
Childhood obesity represents a significant public health challenge, involving a combination of factors related to diet, social context, and psychological aspects. Research shows that the high consumption of ultra-processed foods and the absence of effective dietary guidance contribute to this problem, especially in areas with greater economic vulnerability. The adoption of preventive measures, through nutritional education in educational institutions and support for families, is crucial to cultivate healthier habits. It is necessary for public policies to increase access to healthy food options and promote regulation on food advertising. A strategy that brings together different disciplines and areas of activity is vital to create favorable environments that encourage healthy choices and help in the full development of children.